1994
DOI: 10.1111/j.1432-1033.1994.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Autophosphorylation Site in the Platelet‐Derived Growth Factor α Receptor from a Heterodimeric Receptor Complex

Abstract: The platelet-derived growth factor (PDGF) a and p receptors undergo dimerization as a consequence of ligand binding. Depending on the PDGF isoform (PDGF-AA, -AB or -BB), homodimers or heterodimers of receptors are formed. In this study, we have used transfected porcine aortic endothelial cells, coexpressing cDNAs for the a receptor and the p receptor at comparable levels, to investigate the properties of the up-heterodimeric receptor complex. PDGF-AB, which mainly induced ap-heterodimeric complexes, was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 60 publications
5
35
0
2
Order By: Relevance
“…The PDGF-AB isoform has been reported to possess the strongest ability to induce a mitogenic response in cells expressing both a-and b-receptors (Heidaran et al, 1991;Rupp et al, 1994). We have therefore investigated the possible unique features of the heterodimeric PDGF receptor complex compared to the homodimeric complexes, and found that in the heterodimeric complex activation of Ras and Erk2 MAP kinase were stronger and more sustained compared to homodimeric complexes (Ekman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The PDGF-AB isoform has been reported to possess the strongest ability to induce a mitogenic response in cells expressing both a-and b-receptors (Heidaran et al, 1991;Rupp et al, 1994). We have therefore investigated the possible unique features of the heterodimeric PDGF receptor complex compared to the homodimeric complexes, and found that in the heterodimeric complex activation of Ras and Erk2 MAP kinase were stronger and more sustained compared to homodimeric complexes (Ekman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PDGF-CC and PDGF-DD have been shown to activate ␤-and ␣-receptors, respectively, in cells expressing both receptor types [87][88][89][90]. The PDGF-AB isoform has been reported to possess the strongest ability to induce a mitogenic response in cells expressing both ␣-and ␤-receptors [91,92].…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…PDGFR can form a heterodimeric receptor complex between the a and b receptors (Rupp et al 1994). In addition, PDGFRA and PDGFRB can also form heterodimers with other RTK family members, as demonstrated for FGF-R1 and EGFR, respectively (Saito et al 2001;Faraone et al 2006).…”
Section: The Kp Fusion Can Form Homodimers and Heterodimers In A Ligamentioning
confidence: 99%